The Concept of Modeling the Risk of Green Building Implementation and their Impact on the Application of the Pentuple Bottom Line: Literature Review - Susanto, Sony; Ciptadi, Gatot; Hanani, Nuhfil; Anwar, M. Ruslin; Marjono, Marjono (Postgraduate School of Universitas Brawijaya, 2023)
Construction is the most significant contributor to global energy consumption. Several studies are currently being conducted to assess the risk of green construction projects, and risk modeling that considers sustainable variables is required. This study aims to evaluate, assess, and analyze the current literature on the concept of modeling the risk of green on the application of the pentuple bottom line, as well as to identify the associated themes and gaps. The Scopus databases were searched for risk green buildings using keywords such as